TI_GERICHTE 11.2021.43 vom 9. März 2022 , Proprietà per piani: nullità o annullamento di risoluzione assembleare - TI Tribunale d'appello (2022)
Proprietà per piani: nullità o annullamento di risoluzione assembleare